PEMENUHAN HAK ANAK BERKEBUTUHAN KHUSUS DALAM IMPLEMENTASI PROGRAM PENDIDIKAN INKLUSIF DI SDN 20 MATARAM - Ni Luh Putu Nina Sri Warthini; Ketut Sri Kusuma Wardani; Aisa Nikmah Rahmatih; Nurwahidah Nurwahidah; Fitri Puji Astria (PROGRES PENDIDIKAN, 2020)
This study aims to determine the fulfillment of the rights of children with special needs (ABK) in SDN 20 Mataram. This research is a qualitative descriptive study. Data collection is done by observation, interviews and questionnaires. The research subjects were the principal, class teachers and special assistant teachers (GPK). Data analysis was performed by using data reduction, data display, and conclusion drawing methods. The results showed that SDN 20 Mataram had implemented the concept of inclusive education quite well, shown by the ABK rights that had been generally fulfilled in accordance with government regulation No. 72 of 1991